Revaskularisasi gigi : Prosedur Perawatan Potensial untuk Regenerasi Gigi Nekrosis Pulpa Apeks Terbuka (Tinjauan Pustaka) - Tien Suwartini (Jurnal Kedokteran Gigi Terpadu, 2019)
Background: Endodontic treatment of young permanent (immature) necrosis  teeth is often challenging because the condition of thin and short roots increases the risk of fracture during  treatment. Review: The optimum healing condition for teeth with open apex necrotic pulp is to regrow functional pulp tissue and continued root development. A novel concept of revascularization of immature nonvital, infected teeth was recently introduced. Conclusions: This paper summarizes the literature supporting biological reasons for considering revascularization procedures for immature permanent teeth with pulp necrosis and the future potential of regenerating the pulp tissue as a routine dental procedure